Pengaruh Current Ratio, Debt to Equity Ratio, dan Rasio Profitabilitas terhadap Harga Pasar Saham LQ45 - Muhammad Irfani Faisal; Padlah Riyadi (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research was to determine the influences of Current Ratio, Debt to Equity Ratio, Return on Equity, and Earnings per Share to stock market price in the LQ45 Companies. The sample used in this study is LQ45 index of companies listed on the Indonesia Stock Exchange period 2020 to 2022. The method of sample selection in this research using purposive sampling method. The number of companies sample in this study is 20 companies with the observation period of three years, so that the selected of 60 observation. The data used in this research is secondary data. Data analysis technique used is multiple linear regression analysis. The test results indicate that Return on Equity and Earnings per Share have a significant influence on stock market price, while the Current Ratio and Debt to Equity Ratio have not significant influence on stock market price in LQ45 index of companies listed on the Indonesia Stock Exchange.